Golden Middle Ages in Europe : new research into early-medieval communities and identities : proceedings of the second 'Dorestad congress' held at the National Museum of Antiquities Leiden The Netherlands 2-5 July, 2014 - Dorestad congress 2014 : Leiden); Kik, Hanneke, 1979-; Willemsen, Annemarieke (Johanna Maria Frederika), 1969- (Turnhout : Brepols, 2015)
In July 2014, the National Museum of Antiquities in Leiden hosted the second Dorestad congress, exactly five years after the first. This congress was attached to the exhibition Golden Middle Ages: The Netherlands in the Merovingian World, 400-700 AD and brought together scholars to discuss these 'Dark Ages', their burials and settlements, rituals and identities, and the position of the Low Countries in the world-wide networks of early-medieval Europe. The congress opened with a keynote lecture by dr. Gareth Williams (The British Museum). Sessions were devoted to key themes like early-medieval identity and agency, so-called royal burials in Europe, significant find categories like garnets, coins and Merovingian glass, important new sites and finds from the Low Countries and recent work in the Carolingian ‘vicus famosus’ of Dorestad.
Keywords: Medeltiden; Antiquities; Fornlämningar; Merovingians -- Netherlands -- Congresses; Dorestad (Extinct city) -- Congresses; Europe -- History -- 392-814 -- Congresses; Nederländerna -- Dorestad; Netherlands -- Antiquities -- Congresses; Netherlands -- History -- To 1384 -- Congresses